Uma proposta de sequência didática para os pontos quânticos no ensino médio - Silva, Carla Caroline Melgueira da (2024)
This proposed didactic sequence on Quantum Dots was applied to a 2nd grade high school class, made up of 44 students in the year 2022 and the last part of this didactic sequence was applied to that same class, already in 3rd grade of high school in 2023, in the morning shift, at a Public School in Manaus. This didactic sequence required five (05) classes lasting 50 minutes each, the objective of which was to provide students with an understanding of the topic of quantum dots and their applications in the development of new technologies in various areas. To prepare this didactic sequence, several didactic resources were used to facilitate students' learning throughout classes, such as the use of slides, short videos on the topic covered, the use of scientific articles and materials from technology websites that address this topic, a conversation with students so that they could explain what they learned about quantum dots and their applications in everyday life. The students were divided into several teams, with a maximum of five members, and a digital game called Show do Milhão dos QDs was created for this approach. The framework adopted in this work was David Ausubel's Meaningful Learning Theory (TAS) and the approach used in this didactic sequence was the Science, Society, Technology and Environment (CSTA) approach, with the aim of showing how the use of technology points Quantum technology can help solve problems faced by society. Information on students' knowledge regarding this topic was collected through two questionnaires, an initial questionnaire consisting of four open questions, to determine whether there was any prior knowledge on the part of these students regarding this topic, in addition to a final questionnaire consisting of five open and closed questions, with the aim of verifying whether there was an evolution in the learning process in relation to this topic. In addition to the proposal for the digital game “Show of the million QDs”, to assist in the learning process of the students involved in this approach, an evaluation questionnaire for this digital game was also used, present in the didactic sequence.